Attitude of Medical Technology Students at University of Zawia Toward Smoking on Their Oral Health Care - Awatef Al-Gadhi,; Khawla Al-Grew,; Khoulod Agina, (AlQalam Journal of Medical and Applied Sciences, 2024)
The use of tobacco has been linked to the etiology and increase severity of adverse effects on oral health, ranged from the discoloration that happened for tooth to the periodontal disease like gingivitis and periodontitis.This study was conducted within the faculty of medical technology in Zawia , and the number of student who participated in the study was73 students were selected to get their answers to the questions raised and excluded some of them for not giving them appropriate answers.This was comparative study whereby the oral status of smoker and non-smoker was compared, it involves just males setting adolescent and adults volunteers aged 18-30 were recruited.Current smokers were in turn interviewed about their duration of smoking and appropriate number of cigarette they smoked per day and non-smoker were interviewed on the same question that asked to the smokers which was about the oral health status.Among 60 respondents were 32 smokers and 28 non-smokers.Halitosis was diagnosed in 22 subjects. 15 (46.875%) of whom were smoker. 7 (25%) of never smokers and have halitosis. And about gingivitis, our study shows that 15 smokers appear to have gums with a good color and appearance compared to 16 non-smokers gums appear rosy, 13 smokers appear gums in red compared to 9 non-smokers have redness in the gums.Gingivitis may develop in advanced stages to include plaque buildup below the gum line, affecting the tooth bone and supporting tissues which are called periodontitis, about this section we noticed that 6 smokers said that they lost their teeth compared to 9 non-smokers. Been to find that the majority of members of the study they have good oral hygiene, and thus the number of people with oral diseases was limited, also smoking was no significant effect on the development of disease of the mouth. ارتبط استخدام التبغ بعلم الأسباب وزيادة شدة الآثار السلبية على صحة الفم، والتي تتراوح من تغير اللون الذي يحدث للأسنان إلى أمراض اللثة مثل التهاب اللثة والتهاب دواعم الأسنان. أجريت هذه الدراسة داخل كلية التكنولوجيا الطبية في الزاوية، وكان عدد الطلاب الذين شاركوا في الدراسة 73 طالبًا تم اختيارهم للحصول على إجاباتهم على الأسئلة التي أثيرت واستبعد بعضهم لعدم إعطائهم إجابات مناسبة. كانت هذه دراسة مقارنة تمت من خلالها مقارنة الحالة الفموية للمدخنين وغير المدخنين، وهي تنطوي فقط على تعيين متطوعين من الذكور والمراهقين والبالغين الذين تتراوح أعمارهم بين 18 و 30 عامًا. تمت مقابلة المدخنين الحاليين بدورهم حول مدة التدخين والعدد المناسب من السجائر التي يدخنونها يوميًا وتمت مقابلة غير المدخنين حول نفس السؤال الذي طرح على المدخنين والذي كان حول الحالة الصحية للفم. من بين 60 مستجيبًا كان هناك 32 مدخنًا و 28 غير مدخن. تم تشخيص رائحة الفم الكريهة في 22 موضوعًا. 15 (46.875%) منهم مدخنون. 7 (25%) من غير المدخنين يعانون من رائحة الفم الكريهة. وفيما يتعلق بالتهاب اللثة، أظهرت دراستنا أن 15 من المدخنين يبدو أن لديهم لثة ذات لون ومظهر جيد مقارنة بـ 16 من غير المدخنين تبدو اللثة وردية، و13 من المدخنين تبدو اللثة حمراء مقارنة بـ 9 من غير المدخنين لديهم احمرار في اللثة. وقد يتطور التهاب اللثة في مراحل متقدمة ليشمل تراكم البلاك أسفل خط اللثة، مما يؤثر على عظم الأسنان والأنسجة الداعمة والتي تسمى التهاب دواعم السن، وفي هذا القسم لاحظنا أن 6 من المدخنين قالوا إنهم فقدوا أسنانهم مقارنة بـ 9 من غير المدخنين. لقد وجدنا أن غالبية أعضاء الدراسة لديهم نظافة فم جيدة، وبالتالي كان عدد الأشخاص المصابين بأمراض الفم محدودًا، كما لم يكن للتدخين تأثير كبير على تطور أمراض الفم